Relevance of the time interval between surgery and adjuvant radio (chemo) therapy in HPV-negative and advanced head and neck carcinoma of unknown primary (CUP) - Balk, Matthias; Rupp, Robin; Mantsopoulos, Konstantinos; Allner, Moritz; Grundtner, Philipp; Müller-Hübner, Sarina Katrin Ursel; Traxdorf, Maximilian; Eckstein, Markus; Speer, Stefan; Semrau, Sabine; Fietkau, Rainer; Iro, Heinrich; et al. (BMC Cancer, 2021)
Introduction In contrast to head and neck squamous cell carcinoma (HNSCC), the effect of treatment duration in HNSCC-CUP has not been thoroughly investigated. Thus, this study aimed to assess the impact of the time interval between surgery and adjuvant therapy on the oncologic outcome, in particular the 5-year overall survival rate (OS), in advanced stage, HPV-negative CUPs at a tertiary referral hospital. 5-year disease specific survival rate (DSS) and progression free survival rate (PFS) are defined as secondary objectives. Material and methods Between January 1st, 2007, and March 31st, 2020 a total of 131 patients with CUP were treated. Out of these, 59 patients with a confirmed negative p16 analysis were referred to a so-called CUP-panendoscopy with simultaneous unilateral neck dissection followed by adjuvant therapy. The cut-off between tumor removal and delivery of adjuvant therapy was set at the median, i.e. patients receiving adjuvant therapy below or above the median time interval. Results Depending on the median time interval of 55 days (d) (95% CI 51.42-84.52), 30 patients received adjuvant therapy within 55 d (mean 41.69 d, SD = 9.03) after surgery in contrast to 29 patients at least after 55 d (mean 73.21 d, SD = 19.16). All patients involved in the study were diagnosed in advanced tumor stages UICC III (n = 4; 6.8%), IVA (n = 27; 45.8%) and IVB (n = 28; 47.5%). Every patient was treated with curative neck dissection. Adjuvant chemo (immune) radiation was performed in 55 patients (93.2%), 4 patients (6.8%) underwent adjuvant radiation only. The mean follow-up time was 43.6 months (SD = 36.7 months). The 5-year OS rate for all patients involved was 71% (95% CI 0.55-0.86). For those patients receiving adjuvant therapy within 55 d (77, 95% CI 0.48-1.06) the OS rate was higher, yet not significantly different from those with delayed treatment (64, 95% CI 0.42-0.80; X-(1)(2) = 1.16, p = 0.281). Regarding all patients, the 5-year DSS rate was 86% (95% CI 0.75-0.96). Patients submitted to adjuvant treatment in less than 55 d the DSS rate was 95% (95% CI 0.89-1.01) compared to patients submitted to adjuvant treatment equal or later than 55 d (76% (95% CI 0.57-0.95; X-(1)(2) = 2.32, p = 0.128). The 5-year PFS rate of the entire cohort was 72% (95% CI 0.59-0.85). In the group < 55 d the PFS rate was 78% (95% CI 0.63-0.94) and thus not significantly different from 65% (95% CI 0.45-0.85) of the group >= 55 d; (X-(1)(2) = 0.29, p = 0.589). Conclusions The results presented suggest that the oncologic outcome of patients with advanced, HPV-negative CUP of the head and neck was not significantly affected by a prolonged period between surgery and adjuvant therapy. Nevertheless, oncologic outcome tends to be superior for early adjuvant therapy.
CRIS-Team WoS Importer:2021-12-03